Avocado‐derived avocadyne is a potent inhibitor of fatty acid oxidation. Issue 3 (16th August 2021) - Tcheng, Matthew; Minden, Mark D.; Spagnuolo, Paul A.
Abstract: Avocatin‐B (Avo‐B), an avocado‐derived 1:1 mixture of the polyhydroxylated alcohols avocadyne (AYNE) and avocadene, eliminated leukemia cells by suppressing fatty acid oxidation (FAO) in vivo and in vitro while sparing healthy blood cells. In this study, we identified AYNE as the most potent FAO inhibitor within the Avo‐B mixture capable of inducing cell death in leukemia cells lines (IC50 : 3.10 ± 0.14 µM in TEX cells; 11.53 ± 3.32 µM in OCI‐AML2) and patient‐derived acute myeloid leukemia cells. When added individually, the two Avo‐B constituents demonstrated antagonism (Combination Index values >1), highlighting the need for future studies to assess AYNE alone. Together, this work highlighted AYNE as the most potent FAO inhibitor within the Avo‐B mixture. Practical applications: This work identifies which of the two molecules in avocatin B (Avo‐B), an avocado‐derived mixture of two molecules with demonstrated human safety, utility against leukemia, insulin resistance and diabetes, is most useful. Therefore, it provides the basis for future clinical studies that will focus on testing and developing the most active Avo‐B constituent. Abstract : Avocadyne was the most potent inhibitor of fatty acid oxidation tested.